Genotypic and Phenotypic Characterization of Novel Sequence Types of Carbapenem-Resistant Acinetobacter baumannii, With Heterogeneous Resistance Determinants and Targeted Variations in Efflux Operons - Bharathi, Srinivasan Vijaya; Venkataramaiah, Manjunath; Rajamohan, Govindan (Frontiers in Microbiology, 2021)
Acinetobacter baumannii has emerged as one of the dominant nosocomial human pathogens associated with high morbidity and mortality globally. Increased incidences of carbapenem-resistant A. baumannii (CRAB) have resulted in an enormous socioeconomic burden on health-care systems. Here, we report the genotypic and phenotypic characterization of novel ST1816 and ST128 variants in A. baumannii strains belonging to International clone II (GC2) with capsule types KL1:OCL8 and KL3:OCL1d from India. Sequence analysis revealed the presence of diverse virulome and resistome in these clinical strains, in addition to islands, prophages, and resistance genes. The oxacillinase blaOXA–23detected in the genomic island also highlighted the coexistence of blaOXA–66/blaOXA–98, blaADC73/blaADC–3, and blaTEM–1D in their mobile scaffolds, which is alarming. Together with these resistance-determining enzymes, multidrug efflux transporters also harbored substitutions, with increased expression in CRAB strains. The hotspot mutations in colistin resistance-conferring operons, PmrAB, LpxACD, and AdeRS, were additionally confirmed. Phenotype microarray analysis indicated that multidrug-resistant strains A. baumannii DR2 and A. baumannii AB067 preferred a range of antimicrobial compounds as their substrates relative to the other. To our knowledge, this is the first comprehensive report on the characterization of A. baumannii variants ST1816 and ST128, with different genetic makeup and genome organization. The occurrence of CRAB infections worldwide is a severe threat to available limited therapeutic options; hence, continued surveillance to monitor the emergence and dissemination of such novel ST variants in A. baumannii is imperative.